The status quo, contributors, consequences and models of digital overuse/problematic use in preschoolers: A scoping review - Wang, Chenggong; Qian, Haoyue; Li, Hui; Wu, Dandan (Frontiers in Psychology, 2023)
Digital devices play a critical role in preschoolers’ learning and development. Despite the evidence that digital devices use may facilitate preschoolers’ learning and development, their overuse/problematic use has become a global concern as the popularity and widespread use of digital devices. This scoping review aims to synthesize the empirical evidence to identify the status quo, influential factors, developmental outcomes, and models of overuse/problematic use in preschoolers. This search has identified 36 studies published in international peer-reviewed journals during 2001–2021, converging into four common topics: the current situation, the influential factors, the consequences, and the models. First, the average percentages of overuse and problematic use across the studies collected in this research were 48.34%, and 26.83%, separately. Second, two influential factors were identified: (1) children’s characteristics and (2) parental and family factors. Third, early digital overuse/problematic use was found to have a negative impact on the following domains: (1) physical health, (2) psychosocial health, (3) problematic behaviors, and (4) cognitive development; Fourth, most relevant studies adopted general linear models, while few of them adopted experimental designs. Finally, the implications for future studies and practical improvements are also addressed.